Filippino Lippi : an abundance of invention. - Nelson, Jonathan K. (Renaissance lives., 2022)
The first focused study of Filippino Lippi in a generation, and the first in English in over eighty years, this book presents a new understanding of the Renaissance master-artist. Celebrated as ingenious by Vasari in 1550, Filippino was highly praised and influential, then fell out of favour and was forgotten for centuries. He was rediscovered by the poet Swinburne, who in 1868 celebrated the painters inventive enjoyment and indefatigable fancy. In a similar spirit, this volume explores Filippinos creativity in solving artistic problems. If a Roman cardinal requested a classically inspired work or a Florentine humanist wanted to dazzle observers with his antiquarian interests, Filippino had the sensitivity to understand these diverse needs and express them with highly original solutions.